Analisis Semiotika Charles Sanders Peirce pada Film "Budi Pekerti" Karya Wregas Bhanuteja - Magefira, Andi Nurul; Lanta, Jumiati; Yusmah; Rasyid, Rustam Efendy (Edukasi Lingua Sastra, 2025)
This study aims to describe the forms of icons, indexes, and symbols based on Peirce's semiotics in the film "Andragogy” by Wregas Bhanuteja. The formulation of the research problem is how the forms of icons, indexes, and symbols of Peirce's semiotics are in the film "Andragogy". The approach to this research is a descriptive qualitative type. Data in the form of iconic signs, indexes, and symbols in scenes from the film "Andragogy" by Wregas Bhanuteja. The data source for this research comes from a film that premiered on the Netflix application on March 21, 2024, entitled "Andragogy". The data collection technique for this research is observing, recording, and documenting. The data analysis technique is carried out by data reduction, data presentation, and drawing conclusions. The results of this study are index data that dominates the signs in the film. Then, the icon and index data are the minimum data found in the film “Andragogy”.